Epoxide Hydrolases and their Application in Organic Synthesis - Kotik, Michael; Archelas, Alain; Wohlgemuth, Roland (Current Organic Chemistry, 2012)
The number of synthetic applications of epoxide hydrolases in organic chemistry has reached a remarkable level. This has been due to a tremendous amount of work dedicated to the discovery of novel epoxide hydrolases from various biological sources, understanding the structure and function of these widespread enzymes and last but not least, the stabilization of these biocatalysts by various means for production purposes.
Keywords: chlorohydrins